Preliminary result of rapid solenoid for controlling heavy-ion beam parameters of laser ion source. (13th March 2015) - Okamura, Masahiro; Sekine, Megumi; Ikeda, Shunsuke; Kanesue, Takeshi; Kumaki, Masafumi; Fuwa, Yasuhiro
Abstract To realize a heavy-ion inertial fusion (HIF) driver, we have studied a possibility of laser ion source (LIS). A LIS can provide high-current high-brightness heavy-ion beams; however, it was difficult to manipulate the beam parameters. To overcome the issue, we employed a pulsed solenoid in the plasma drift section and investigated the effect of the solenoid field on singly charged iron beams. The rapid ramping magnetic field could enhance limited time slice of the current and simultaneously the beam emittance changed accordingly. This approach may also be useful to realize an ion source for HIF power plant.